Canine sperm thermoresistance in diluted fresh semen - Sánchez Riquelme, Alfonso (2019)
In order to compare the effect of two types of seminal extenders, physiological saline (PS) and skim-milk (SM), on the functionality of canine spermatozoa in fresh semen subjected to a thermo-resistance test (TRT), 15 ejaculates were obtained by manual massage on the caudal portion of the bulb of the glans penis. Fifteen males, clinically healthy, of different small and medium breeds were used, all with proven fertility. The second fraction of each ejaculate was collected. The seminal evaluation considered progressive motility (PM) and membrane functionality with a simplified hypoosmotic test (HOST-s). Then, from each ejaculate, aliquots of 100 μl of semen were taken to be diluted in 200 μl of PS and SM respectively and then incubated at 38 °C for 30 minutes (TRT). As control, 300 μl of undiluted fresh semen was incubated. Next, PM and HOSTs were evaluated. The PM in the fresh semen was 81.4 ± 8.1 and the response to the HOST-t 94.0 ± 7.80, both values higher than those observed after the TRT in the diluted samples (p<0.05). However, when comparing both diluents after the TRT, no significant differences were observed: PS (PM: 71.0 ± 27.2 and HOST-s: 87 ± 10.5%) and SM (PM: 69.0 ± 18.5 and HOST-s: 86.0 ± 10.6%).